2018
DOI: 10.3802/jgo.2018.29.e48
|View full text |Cite
|
Sign up to set email alerts
|

Impact of lymph node ratio on survival in stage IIIC endometrioid endometrial cancer: a Turkish Gynecologic Oncology Group study

Abstract: ObjectiveThe purpose of this study was to investigate the prognostic value of lymph node ratio (LNR) in women with stage IIIC endometrioid endometrial cancer (EC).MethodsA multicenter, retrospective department database review was performed to identify patients with stage IIIC pure endometrioid EC at 6 gynecologic oncology centers in Turkey. A total of 207 women were included. LNR, defined as the percentage of positive lymph nodes (LNs) to total nodes recovered, was stratified into 2 groups: LNR1 (≤0.15), and L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…NPLN was divided into NPLN1 (1), NPLN2 (2-6), and NPLN3 (≥7). NNLN was categorized as NNLN1 (<5), NNLN2 (5)(6)(7)(8)(9)(10)(11)(12)(13), and NNLN3 (≥14). LNR was classified into LNR1 (0.01-0.15), LNR2 (0.16-0.66), and LNR3 (≥0.67).…”
Section: Data Source and Population Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…NPLN was divided into NPLN1 (1), NPLN2 (2-6), and NPLN3 (≥7). NNLN was categorized as NNLN1 (<5), NNLN2 (5)(6)(7)(8)(9)(10)(11)(12)(13), and NNLN3 (≥14). LNR was classified into LNR1 (0.01-0.15), LNR2 (0.16-0.66), and LNR3 (≥0.67).…”
Section: Data Source and Population Selectionmentioning
confidence: 99%
“…This new N staging principle made sense from the perspective of regional LN drainage, as the pelvic LN basin harbored almost all of the uterine LN drainage while the para-aortic LN involvement might imply further progression (8,9). However, this staging system did not take LN number or ratio into consideration, and previous studies have revealed that a higher number of positive lymph nodes (NPLN) or lymph node ratio (LNR) was related to more dreadful survival for EEC patients (10)(11)(12). So, it is necessary to further explore the prognostic significance of these LN schemes.…”
Section: Introductionmentioning
confidence: 99%
“…Retroperitoneal LN assessment remains an essential component of the surgical staging of patients with intermediate to high‐risk EC 15,18 . However, the therapeutic value of LND for EC remains a matter of debate 15,16 .…”
Section: Discussionmentioning
confidence: 99%
“…All patients underwent surgical staging with total hysterectomy ± bilateral salpingo-oophorectomy, pelvic and paraaortic lymphadenectomy, infracolic omentectomy and peritoneal washings by gynecologic oncologists. Lymph node dissection was performed as previously described (14). Adequate pelvic and para-aortic lymphadenectomy have been defined as removal of at least 10 pelvic lymph nodes (LNs) and at least 5 para-aortic LNs (15)(16)(17).…”
Section: Methodsmentioning
confidence: 99%